Recent acquisition of Helicobacter pylori by Baka pygmies. - Sandra Nell; Daniel Eibach; Valeria Montano; Ayas Maady; Armand Nkwescheu; Jose Siri; Wael F Elamin; Daniel Falush; Bodo Linz; Mark Achtman; Yoshan Moodley; Sebastian Suerbaum (PLoS Genetics, 2013)
Both anatomically modern humans and the gastric pathogen Helicobacter pylori originated in Africa, and both species have been associated for at least 100,000 years. Seven geographically distinct H. pylori populations exist, three of which are indigenous to Africa: hpAfrica1, hpAfrica2, and hpNEAfrica. The oldest and most divergent population, hpAfrica2, evolved within San hunter-gatherers, who represent one of the deepest branches of the human population tree. Anticipating the presence of ancient H. pylori lineages within all hunter-gatherer populations, we investigated the prevalence and population structure of H. pylori within Baka Pygmies in Cameroon. Gastric biopsies were obtained by esophagogastroduodenoscopy from 77 Baka from two geographically separated populations, and from 101 non-Baka individuals from neighboring agriculturalist populations, and subsequently cultured for H. pylori. Unexpectedly, Baka Pygmies showed a significantly lower H. pylori infection rate (20.8%) than non-Baka (80.2%). We generated multilocus haplotypes for each H. pylori isolate by DNA sequencing, but were not able to identify Baka-specific lineages, and most isolates in our sample were assigned to hpNEAfrica or hpAfrica1. The population hpNEAfrica, a marker for the expansion of the Nilo-Saharan language family, was divided into East African and Central West African subpopulations. Similarly, a new hpAfrica1 subpopulation, identified mainly among Cameroonians, supports eastern and western expansions of Bantu languages. An age-structured transmission model shows that the low H. pylori prevalence among Baka Pygmies is achievable within the timeframe of a few hundred years and suggests that demographic factors such as small population size and unusually low life expectancy can lead to the eradication of H. pylori from individual human populations. The Baka were thus either H. pylori-free or lost their ancient lineages during past demographic fluctuations. Using coalescent simulations and phylogenetic inference, we show that Baka almost certainly acquired their extant H. pylori through secondary contact with their agriculturalist neighbors.